The stallion - Robbins, Harold (London : New York : Pocket Books, 1996)
Continuing the phenomenal story in The Betsy, The Stallion reintroduces the Hardeman family and the cut-throat world of their vast automobile empire.
Keywords: v; Automobile industry and trade